Scholarly Journals at the Periphery: the case of Croatia - Hebrang Grgić, Ivana (2014)
This paper analyses 231 Croatian journals available on the national online platform, the Hrčak portal. To qualify for analysis journals had to be peer reviewed and to have published at least one issue in 2012. Some differences from the results of previous studies were noted. More journals are internationally oriented and the number of times they are accessed apparently depends on their scientific field. Publishers are still mostly not-for-profit but are more likely now to apply article processing/publication charges. This is new for Croatia and raises questions about the potential influence of this trend on the availability and visibility of scientific results. The results are relevant not only to Croatia but may also be representative of other countries at the ‘periphery’.
ENG